DETERMINATION OF THE FINANCIAL RESULT IN THE INSURANCE AND REINSURANCE COMPANIES CONSIDERING THE ACCOUNTING ACT - Katarzyna Świetla; Krzysztof Jonas (Zeszyty Naukowe Wyższej Szkoły Finansów i Prawa w Bielsku-Białej, 2016)
The procedure of determining the financial result in the insurance companies significantly differs from the rules set for a typical entity. The paper, using the example of the report-the profit and loss account presents the principles for determining both the technical and overall profit and loss account discussing individual categories. The paper has indicated categories concerning revenues and costs specific only for the insurance companies.